If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying D = vb + tb Reorder the terms: D = bt + bv Solving D = bt + bv Solving for variable 'D'. Move all terms containing D to the left, all other terms to the right. Simplifying D = bt + bv
| (16-2x)(11-2x)=86 | | 0.5x^2-2x+6=0 | | 4-7g=h+4 | | 1/3x-16=14 | | 5x+4-x=-6 | | -5(1+8x)=-205 | | 8=27x | | p=86.3ln(h-690) | | (4c)12+(3b)7= | | .5t+9=1 | | 5(3x-6)-4(x+2)-17x= | | 3b(6b+4)= | | 1.3x=5.72 | | 4/15=x/6 | | 4c*12+3b*7= | | 8(w+4)=w(w-2)(w+4) | | -4(-6+5)-7=93 | | D/8=2 | | 4w^2+37w+35=0 | | -24x=-15x | | -20b=320 | | 3y-9+2x=3x | | 2n=m | | (4W^2-6W+2)+(-7W^2+3W+1)= | | 3x+3y=8*2x | | 6y+18=8y | | 6.4x-1.7=11.1 | | (4c*12)+(3b*7)= | | -0.625x+.25=0.125 | | -0.625x+.25=0125 | | k/2-9/4 | | 6(3x-1)=19 |